Opium's orphans : the 200-year history of the war on drugs - Caquet, P. E. (Reaktion Books Ltd, 2022)
"Opium's Orphans is the first full history of drug prohibition and the 'war on drugs'. A no-holds-barred but balanced account, it shows that drug suppression was born of historical accident, not rational design. The war on drugs did not originate in Europe or the USA, and even less with President Nixon, but in China. Two Opium Wars, followed by Western attempts to atone for them, gave birth to an anti-narcotics order that has come to span the globe. But has the war on drugs succeeded? As opioid deaths and cartel violence run rampant, contestation becomes more vocal and marijuana is slated for legalization in many places, Opium's Orphans proposes that it is time to go back to the drawing board."--